Memory Game Intervention in Improving Cognitive Ability and Memory in Elderly with Dementia: A Literature Review - Retti Dwitria Wilda; Sukihananto (LPPM STIKES Al-Ma'arif Baturaja, 2024)
Dementia is a disorder that results in a decline in memory and cognitive function, and can interfere with daily activities. There needs to be interventions that can help prevent dementia, and one effective intervention is memory games, that can be accessed through devices such as smartphones and computers with animations and sounds that help improve memory performance and can be used for early screening of dementia symptoms. The purpose of this literature review is to explore the benefits of brain training apps and computer – based cognitive training as nursing interventions to improve cognitive function and prevent dementia in elderly. Method : used in this literature review is systematic study by collecting and analyzing relevant literature related to the research topic. Keywords used are dementia, elderly, brian-memory game, memory game, app-based game, virtual reality, cognitive impairment. Academic journals were searched through online databases such as ClinicalKey Nursing, Google Scholar, Proquest, ScienceDirect, and EMBASE from 2015-2023. Results : this Literature Review show that brain training apss and computer based cognitive training can be effective nursing interventions to improve cognitive function and prevent dementia in the elderly. Several articles analyzed show that brain training apps and computer-based cognitive training can help improve cognitive function in the elderly, especially in terms of memory and attention. In addition, brain training apps and computer – based cognitive training can also help prevent dementia symptoms in the elderly and improve their quality of life by increasing their ability to perform daily activities. Conclusion : Nurses and healthcare professionals can utilize brain training apps and computer-based cognitive training as one way to improve the quality of life for the elderly. However, it is important to note that brain training apps and computer-based cognitive training should be tailored to the needs and characteristicts of the elderly to provide optimal benefits.